Humor: Yes. it is possible to translate it and teach how to translate it - Brezolin, Adauri (TradTerm, 1997)
The present paper aims at presenting an answer to the question posed by John Robert Schmitz in TradTerm 3, 1996. This study will attempt to demonstrate that, taking into account the difficulties inherent to the translational act, it is nevertheless possible to translate humor and to teach how to translate it. With this purpose in mind, we will present an activity conducted with students of translation in which we will try to show some of the (linguistic, pragmatic and cultural) mechanisms utilized in creating humor and how we can proceed to retrieve them and retain the same, or almost the same, humorous effect in the translated text.